Stretchable OLEDs: Realizing Stretchable OLEDs: A Hybrid Platform Based on Rigid Island Arrays on a Stress‐Relieving Bilayer Structure (Adv. Mater. Technol. 11/2020). Issue 11 (10th November 2020) - Kim, Taehyun; Lee, Hyeonwoo; Jo, Woosung; Kim, Taek‐Soo; Yoo, Seunghyup
Abstract : In article number 2000494, Seunghyup Yoo and co‐workers present a hybrid platform for stretchable displays. The proposed platform consists of an array of rigid islands connected by stretchable interconnectors and a bi‐layer elastomer substrate in which the top layer has an ultralow Young's modulus. This low‐modulus top layer greatly relieves the mechanical stress applied to devices yet compatible with key fabrication processes, enabling the realization of stretchable OLEDs with performance comparable to that of conventional, rigid OLEDs.